Analisis Komparatif Kinerja Keuangan Perusahaan Sub Sektor Pariwisata Pada Masa Pandemi Covid-19 - Rizki Ariq Athullah; Marcelia Susan (Universitas Sains dan Teknologi Komputer, 2023)
This study intends to examine the financial performance of tourist industry enterprises listed on the Indonesian stock exchange from 2018 until 2021, both before and after the Covid-19 outbreak. The following indicators of financial ratios are used to assess a company's financial performance: liquidity (Current Ratio and quick ratio), solvency (debt-to-asset ratio and debt-to-equity ratio), activity (total asset turnover and working capital), and profitability (Return On Assets and Return On Equity). The data used in this study is secondary data from Indonesia Stock Exchange in the form of the 2018-2020 Annual Report. 2018 and 2019 financial reports for the situation before the COVID-19 pandemic and 2020 and 2021 annual reports for the situation during the COVID-19 pandemic. According to this study's findings, there are notable differences in the debt-to-equity, debt-to-asset, return-on-asset, return-to-equity, and total asset turnover before and after the COVID-19 pandemic. Meanwhile, the quick ratio and debt-to-equity ratio are not significantly different